Accounting Practices and the Use of Money in the Reign of King Udayana in Bali: An Ethnoarcheological Approach - I GUSTI AYU NYOMAN BUDIASIH; EKO GANIS SUKOHARSONO (The Indonesian Journal of Accounting Research, 2013)
The study takes an ethnoarcheological approach to exploring the existence of accounting practices and the use of money in the reign of King Udayana (during the period 989-1011 Masehi).The period was considered important since it was the golden age of the Singhamandawa Kingdom in Bali where King Udayana successfully integrated Bali and Nusa Tenggara, and its influence reached East Java. King Udayana had a prominent role in the development of the economic, social, political and religious values of the people of Bali. It is concluded that using the ethnoarcheological approach, In the era of King Udayana, some clear pictures of the existence of accounting practices could be drawn. Accounting was understood in the era in various forms, including economic transactions in the traditional markets, the use of currency on many social occasions, and simple models of record keeping. It is also believed that King Udayana used religious values as the basis of people’s social and economic transactions. It is also found that in the reign of King Udayana, money in the form of coins was used intensively. Coins were minted using gold and silver plates as the local currency used strongly reflected the spiritual contexts which were highly respected by local community. The symbols on the coins had two similar patterns which were the same on both the left and right sides; on the gold coins they depicted life which has a balance between outward and inward or material and spiritual concepts. Similarly, the pattern featuring four sandalwood flower petals that was printed on silver currency as a sacred tree. Belief in this spiritual foundation was a very important concept to put into practice in order to obtain a balance between material and spiritual life. It is also believed that the accounting practices performed during the era of King Udayana also used the practice of balance. Transactions related to the use of currency trading were carried out between the kingdom and the villagers, as expressed in the inscription, showed how the empire really understood the meaning of well-being and balanced life.